Ethnic Identity Perception Among Malaysian Urban Tamil Youths Disconnected from Their Heritage Language - Ravindaran Maraya; Bharathi Mutty; Silllalee S. Kandasamy (International Journal of Asia Pacific Studies, 2026)
The phenomenon of language shift among Malaysian Tamils is well documented, highlighting both disconnection and preservation of the Tamil language. However, its impact on the community members’ ethnic identity remains underexplored. This study examines the perceptions of ethnic identity among Malaysian urban Tamil youths disconnected from their heritage language and their negotiation of ethnic identity without linguistic capital. It addresses the underexplored link between language shift and ethnic identity perceptions. This qualitative study involved twenty Malaysian urban Tamil youths who had shifted from their heritage language to English. The data were thematically analysed using Identity Process Theory (continuity, self-esteem, self-efficacy, and distinctiveness) to frame their perceptions of Malaysian Tamil identity. Results showed polarised views. Participants with negative perceptions experienced identity threats, which they negotiated by disengaging from their Tamil identity. In contrast, those with positive perceptions asserted their ethnic identity through non-linguistic markers (food, cultural practices, and clothing). Further analysis of negative perceptions underscored stigma management strategies, wherein the participants distanced themselves from the threatening ethnic identity, resorting to masking or adopting superordinate identities (Malaysian, Indian). In contrast, positive perceptions interpreted through post-ethnic theory revealed the fluidity of ethnic identity formation, extending beyond linguistic markers, and foregrounding the dynamic nature of identity construction in a globalised, multilingual world.